Risk-appropriate regulations for gene-editing technologies - Graham Brookes; Stuart J Smyth (GM Crops & Food, 2024)
This paper explores the scope for the newly emerging technologies, based on gene editing (GE) contributing to addressing the global challenges that we face. These challenges relate to food security, climate change and biodiversity depletion. In particular, it examines the science and evidence behind the most appropriate forms of agricultural production to meet these challenges, the targets set in the Global Biodiversity Framework (GBF) agreed to at the end of 2022 and the possible role of GE technologies in contributing to meeting these targets. It then examines the most risk-appropriate regulatory environment required to best facilitate the adoption of GE technology, drawing on the experiences of the impact of regulatory systems for other innovations used in agricultural and food production systems such as genetically modified organisms (GMOs).